(untitled) (Medical Forum Monthly, 2024)
Objective: The primary objective was to study about different weapon of offence, used in inflicting bodily medico legal injuries in a rural area of Khyber Pakhtoonkhuwa. Materials and Methods: the study is a record based research, 55 cases were selected, which were consecutively recorded from the previously registered MLC cases in a rural area, data of types of weapon used in offences along with preliminaries data was recorded from the record and analyzed. Results: in 55 cases the weapon of offence used were blunt weapon, sharp heavy edged, sharp light edged, Fire arm and road traffic accidents’ there were total 37 ( 67.3%) cases of blunt weapon, of which 31(64.6%) were of male and 6 ( 85.7%) of female, only 1 (2.1%) of male were injured with sharp heavy edged weapon, while non of female was hurted with such weapon, 3 (6.25%) of male and 1 (14.3%) of female were injured by sharp light edged weapon, total of 5.5% were hit by fire arm, and 18.2% cases were of RTA. Conclusions: our study reflect the true picture of rural society where the female population suffered less as compared to male, due to their conservativeness, weapon was used 48 (87.3) times against male population and 7 (12.7) time against female which prove that it is true that, in the society of pathans in KPK province female and children are spared in the enmity disputes.